A Semi-automated Organoid Screening Method Demonstrates Epigenetic Control of Intestinal Epithelial Differentiation - Ostrop, Jenny; Zwiggelaar, Rosalie T.; Terndrup Pedersen, Marianne; Gerbe, François; Bösl, Korbinian; Lindholm, Håvard T.; Díez-Sánchez, Alberto; Parmar, Naveen; Radetzki, Silke; von Kries, Jens Peter; Jay, Philippe; Jensen, Kim B.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Intestinal organoids are an excellent model to study epithelial biology. Yet, the selection of analytical tools to accurately quantify heterogeneous organoid cultures remains limited. Here, we developed a semi-automated organoid screening method, which we applied to a library of highly specific chemical probes to identify epigenetic regulators of intestinal epithelial biology. The role of epigenetic modiers in adult stem cell systems, such as the intestinal epithelium is still undefined. We identified several targets, which were verified by complementary methods, including HDACs, EP300/CREBBP, LSD1, and type I PRMTs. Based on this resource data, we conclude that epigenetic modiers are primarily involved in balancing maturation of the epithelium. Furthermore, we show that inhibiting type I PRMTs, which leads to epithelial maturation, blocks the growth of adenoma but not normal organoid cultures. Thus, epigenetic probes are powerful tools to study intestinal epithelial biology and may have therapeutic potential.